Locating the Subject in Postmodern State: A Critique of Kazuo Ishiguro’s The Remains of the Day (Literary Voice, 2024)
A British novelist of Japanese origin, Kazuo Ishiguro explores the social and political atmosphere of England that unsettled the nation in the decade after World War I. He brings to notice the significant role of an individual’s inner emotional dilemma of the professional self. This paper then offers a close reading of Ishiguro’s The Remains of the Day (1989), exploring the discourse of the subject within a social, political and ideological framework that constructs the concept of selfhood. This play of socio-political ideologies includes subjects that are no more than cultural performances. Centring on Ishiguro’s exploration of this decentred subject, this paper scrutinises the symbolic link between the protagonist Stevens’s selfhood caused by self-deception or the ideological state apparatus and fictional world leaders’ discourse on professionalism. From this viewpoint, the main objective of the paper is to uncover how Ishiguro’s work dramatises the transformation of the modernist preconstituted subject into the postmodernist decentred subject.
Keywords: Kazuo Ishiguro, subject, subjectivity, postmodern, England